(3GdfXQjI GdYGeI ddCMcGe aj GdehGO GdeOfjI hGdJLGQjI hGdCMhGd GdTNUjI abgG hbVGAGs - (3GHQGgje(B, (3SjO CMeOs ((3GdEScfOQjI(B:s (3GdecJH GdLGeYj GdMOjK(B,s, 2004)
(3GdfXQjI GdYGeI ddCMcGe aj aj GdehGO GdeOfjI hGdJLGQjI hGdGCMhGd GdTNUjI , VhGHW JSHjH GdGMcGe GdeOfjI hGdJLGQjI , GdeHGOF GdbVGFjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdbGfhf GdeOfjs